2001
DOI: 10.1080/14622200110040638
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of environmental tobacco smoke in a population of Puerto Rican children

Abstract: This study was designed to determine among various personal, socioeconomic, and environmental factors those which had the greatest influence on exposure to environmental tohacco smoke (ETS) in a population of children residing in a tropical environment and to compare these results with those obtained in the literature of tobacco exposed children in temperate climates. Urine specimens were collected from 606 healthy Puerto Rican children (2-12 years) living in an industrial area and analyzed for cotinine, a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…Gender based stratification revealed slightly higher rates of exposure among males compared with females, which is consistent with the findings of surveys conducted in other countries 11,12 . However, in a former GYTS-based study conducted in Greece by Rachiotis et al 8 , the authors reported that males were less likely to be exposed at home than females.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Gender based stratification revealed slightly higher rates of exposure among males compared with females, which is consistent with the findings of surveys conducted in other countries 11,12 . However, in a former GYTS-based study conducted in Greece by Rachiotis et al 8 , the authors reported that males were less likely to be exposed at home than females.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, we didn't use biomarkers such as urine cotinine in order to evaluate exposure to passive smoking. Such methodology has been shown to be more accurate, since the levels of these biomarkers are strongly correlated with the amount of inhaled tobacco-smoke 11 . conclusIons Current prevalence of exposure to passive smoking among high school students in Greece is extremely high.…”
Section: Discussionmentioning
confidence: 99%
“…Preston et al . in a study among Puerto Rican children found no significant difference between males and females in terms of exposure to ETS [11]. However the previously mentioned finding, if confirmed by future studies, has to be addressed by future research in order to clarify why this difference between sexes in exposure to ETS does exist.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, we did not use biomarkers of exposure to ETS in order to assess the exposure status of the participants. It has been reported that the assessment of exposure status to passive smoking by the use of both questionnaires and biomarkers led to results that differed significantly [11]. The questionnaires are very useful in order to provide information on the population potentially susceptible to exposure to secondhand smoke, while the biomarker reflects the amount of tobacco smoke inhaled, and thus is a more reliable index of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…13 For instance young children are likely to be exposed to ETS at home and maternal smoking is an important risk factor. Older children may be exposed to ETS at home as well as smoking occurring at school, including among teachers, and elsewhere.…”
Section: Discussionmentioning
confidence: 99%